The Transformation Of Chinese Painting In The 20th Century: Western Influence, From Modernism To Post-Modernism - Xu, Peigang
In the 20th century, China experienced profound historical transformation that significantly impacted its art world. A number of significant events took place such as the establishment of the Republic of China, the Second World War and the foundation of the People’s Republic of China. The country saw the reform era which Li Hongzhang described as “unprecedented changes in three thousand years”. There are two clues to the development of Chinese art in the 20th century: modernism and post-modernism. This period featured such prominent artists as Xu Beihong Lin Fengmian, Jiang Zhaohe, Liu Haisu, Wu Dayu and others who had studied abroad. They began promoting the modern transformation of Chinese art, exploring its development and opening up a new era, despite the existing radical views. In 1949, when new China was founded, art served ideology, and a large number of works on revolutionary realism appeared. At the same time, Wu Dayu, the founder of modern Chinese art, played a particularly important role in transformation of Chinese art. 20-րդ դարում Չինաստանը մեծ պատմական փոփոխություններ կրեց, ինչը, բնականաբար անդրադարձավ նաև մշակույթի վրա՝ Չինաստանի Հանրապետության ստեղծումը, Երկրորդ Համաշխարհային պատերազմը, Չինաստանի նոր հանրապետության կազմավորումը: Ինչպես նշում էր Լի Հունչջանը, երեք հազար տարվա ընթացքում Չինաստանն աննախադեպ մեծ փոփոխություններ ապրեց: 20-րդ դարում չինական արվեստում նկատվում է զարգացման երկու ուղղի՝ մոդեռնիզմ և պոստմոդեռնիզմ, որը պայմանավորված էր նաև նրանով, որ անվանի նկարիչներ Սյու Բեյհոնգը, Լին Ֆենգմիանը, Ցզյան Չժաոհեի, Լյու Հայսուն, Վու Դային գեղարվեստական կրթությունը ստացել են արտերկրում: В XX веке Китай пережил большие исторические перемены, что в свою очередь отразилось на искусстве: это создание Китайской Республики, Вторая мировая война и основание Новой Китайской Республики. Как отмечал Ли Хунчжан, за три тысячи лет Китай пережил беспрецедентные изменения. В XX веке в искусстве Китая намечаются две пути развития: модернизм и постмодернизм. Это было обусловлено тем, что известные художники, такие как Сюй Бэйхун, Линь Фэнмянь, Цзян Чжаохэ, Лю Хайсу, У Даю профессиональное художественное образование получили за рубежом.
Keywords: Art